WEBINAR SOSIALISASI PARTISIPASI DEMOKRASI ALA PELAJAR DI SMKN 3 SALATIGA - Kristina Roseven Nababan; Nani Mediatati (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
Participation is an important aspect of democracy as well as the rights of citizens. The implementation of participation is also practiced by students when the emergence of the Criminal Code Bill in 2019 and Omnibus Law in 2020. The purpose of this Community Partnership program is to socialize student-style democratic participation to students of SMK Negeri 3 Salatiga. The specific target to be achieved in this devotional activity is the understanding of the understanding of ethical democracy and the call to critical thinking through media literacy before giving aspirations in democracy. Outside of this activity is scientific publications in the form of Journals as well as posters on Instagram. The method of implementing activities in achieving the objectives of community service is to conduct a webinar on the zoom application with students of SMK Negeri 3 Salatiga.